2006
DOI: 10.1152/ajpcell.00358.2005
|View full text |Cite
|
Sign up to set email alerts
|

ERK/MAPK regulates the Kv4.2 potassium channel by direct phosphorylation of the pore-forming subunit

Abstract: regulates the Kv4.2 potassium channel by direct phosphorylation of the pore-forming subunit. Am J Physiol Cell Physiol 290: C852-C861, 2006. First published October 26, 2005 doi:10.1152 doi:10. /ajpcell.00358.2005.2 is the primary pore-forming subunit encoding A-type currents in many neurons throughout the nervous system, and it also contributes to the transient outward currents of cardiac myocytes. A-type currents in the dendrites of hippocampal CA1 pyramidal neurons are regulated by activation of ERK/MAPK, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
147
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(154 citation statements)
references
References 50 publications
(71 reference statements)
6
147
1
Order By: Relevance
“…In the present study, we have found that in mouse DRG neurons the stimulatory effects of NMU on I A are PKC independent, but rather are mediated by PKA followed by ERK/MAPK. In pyramidal neuron dendrites, activation of ERK leads to reduction of Kv4.2-encoded I A via phosphorylation of Thr-607 in the C-terminal of Kv4.2 (47). However, we have found that in mouse small DRG neurons I A increases after NMUR1 activation and subsequent ERK phosphorylation.…”
Section: Discussioncontrasting
confidence: 64%
“…In the present study, we have found that in mouse DRG neurons the stimulatory effects of NMU on I A are PKC independent, but rather are mediated by PKA followed by ERK/MAPK. In pyramidal neuron dendrites, activation of ERK leads to reduction of Kv4.2-encoded I A via phosphorylation of Thr-607 in the C-terminal of Kv4.2 (47). However, we have found that in mouse small DRG neurons I A increases after NMUR1 activation and subsequent ERK phosphorylation.…”
Section: Discussioncontrasting
confidence: 64%
“…The sh-PTPN5-treated rats showed significantly prolonged duration of stress-induced ERK1/2 activation, as shown by a long-term increase in ERK1/2 and K V 4.2 channel phosphorylation at Thr607 (an increase in phosphorylation level indicates suppression of its activity) (Adams et al, 2000;Schrader et al, 2006) compared with sh-DsRedtreated rats (Fig. 6 A, B).…”
Section: Ptpn5 Loss Of Function Increases Excitatory Overloadmentioning
confidence: 88%
“…Indeed, posttranscriptional mechanisms have been implicated in the regulation of I to,f . 26 Therefore, further experiments in future studies are warranted to explore these issues.…”
Section: Discussionmentioning
confidence: 99%
“…PE/Pro plus Pz did, however, cause small Kv4.2 reductions, similar to that seen with chronic Pro alone, which could originate from inverse agonism of ␤-ARs and the activation of ERK1/2 reported previously for Pro. 18,27 It is tempting to speculate that ERK could mediate the reductions in Kv4.2 expression with Pro alone, because ERKs, as well as mitogen-activated protein kinases (MAPKs) in general, have been implicated in both transcriptional 16 and posttranslational regulation 26 of I to,f . In addition, many stimuli activating MAPK family proteins also activate NF-B.…”
Section: Discussionmentioning
confidence: 99%